Interactions between muscle volume and body mass index on brain structure in the UK Biobank - Lu, Alicia; Than, Stephanie; Beare, Richard; La Hood, Alexandra; Collyer, Taya Annabelle; Srikanth, Velandai; Moran, Chris (Frontiers in Dementia, 2024)
Background Low skeletal muscle volume may increase dementia risk through mechanisms affecting brain structure. However, it is unclear whether this relationship exists outside of sarcopenia and/or varies by other factors. We aimed to study the interplay between skeletal muscle volume and factors, such as age, sex, and body mass index (BMI), in explaining brain structure at midlife in a cohort without sarcopenia. Methods We used abdominal and brain magnetic resonance imaging (MRI) data from a population-based cohort enrolled in the UK Biobank. The following measures were derived: thigh fat-free muscle volume (FFMV), total brain volume (TBV), gray matter volume (GMV), white matter volume (WMV), total hippocampal volume (THV), and white matter hyperintensity volume (WMHV). Participants below sex-based grip strength thresholds suggesting probable sarcopenia were excluded. Linear regression analysis was used to study the interaction or mediation effects of age, sex, and BMI on the associations between FFMV and brain volumes. Results Data were available for 20,353 participants (median age 64 years, 53% female). We found interactions between thigh FFMV, BMI, and age (all p < 0.05). Greater thigh FFMV was associated with better brain volumes in those aged <64 years with normal (TBV: β = 2.0 ml/L, p = 0.004; GMV: β = 0.8 ml/L, p = 0.04; WMV: β = 1.1 ml/L, p = 0.006; WMHV: β = −0.2 ml/L, p = 3.7 × 10−5) or low BMI (TBV: β = 21.2 ml/L, p = 0.003; WMV: β = 13.3 ml/L, p = 0.002, WMHV: β = −1.1 ml/L, p = 0.04). Conclusion Greater thigh muscle volume correlates with better brain volumes at midlife in people without sarcopenia, but this relationship weakens with greater age and BMI. Further study is required to investigate the underlying mechanisms to understand which components of body composition are potentially modifiable risk factors for dementia.